Insulin Treatment Does Not Prevent EARLY Autonomic Cardiovascular and Diastolic Dysfunctions in Streptozotocin-Induced Diabetic Rats - Sarah C. F. Freitas; Marina R. H. Dutra; Paulo M. M. Dourado; Victor Hugo de Martins Miranda; Camila P. dos Santos; Iris C. Sanches; Maria-Cláudia Irigoyen; Kátia De Angelis (MDPI AG, 2024)
Recent studies have found increased cardiovascular mortality risk in patients with type 1 diabetes when compared to normoglycemic people, even when they were kept under good glycemic control. However, the mechanisms underlying this condition have yet to be fully understood. Using streptozotocin (STZ)-induced diabetic rats, we evaluated the effects of insulin replacement therapy on cardiac, autonomic, inflammatory, and oxidative stress parameters. Daily treatment with insulin administrated subcutaneously in the STZ-diabetic rats showed a reduction in hyperglycemia (>250 mg/dL) to normalized values. The insulin treatment was effective in preventing alterations in cardiac morphometry and systolic function but had no impact on diastolic function. Also, the treatment was not able to prevent the impairment of baroreflex-tachycardic response and systolic arterial pressure variability (SAP-V). A correlation was found between improvement of these autonomic parameters and higher levels of IL-10 and lower levels of oxidized glutathione. Our findings show that insulin treatment was not able to prevent diastolic, baroreflex, and SAP-V dysfunction, suggesting an outstanding cardiovascular risk, even after obtaining a good glycemic control in STZ-induced diabetic rats. This study shed light on a relatively large population of diabetic patients in need of other therapies to be used in combination with insulin treatment and thus more effectively manage cardiovascular risk.